DEVELOPMENT OF NEW METHODOLOGIES FOR ROAD ACCIDENT RECONSTRUCTION WITH CDR TOOL - Francisco, André Gaspar (2022)
Road accidents are a constant reality these days, therefore to reduce and understand these accidents and, as a result, improve road safety, an analysis will be carried out on modern and old accident reconstruction methods and how they can be improved. With the new 2022 European Union regulation coming in, which enforces the use of Event Data Recorders (EDR) on newly made vehicles, suddenly there’s a system that can record vehicle dynamic data and driver inputs, in case of an accident. This project’s objective is to analyze this data in an accident context and simplify the reconstruction process. This project aims for a seamless interpretation of the accident scene and vehicle dynamics to better understand the data in the scene’s context. Some methodologies and tools used for the reconstruction of the accident scene will be studied, culminating in a system that digitizes the scene for later use in computer software. The dynamic data from the accident can be divided into three phases: pre-crash, impact, and post-crash. Each phase requires a different approach which depends on the type of data to obtain the trajectory of the vehicle throughout the phases.